A crack model for corroded reinforced concrete elements subject to cyclic loading. Issue 1 (30th March 2022) - Belletti, Beatrice; Vecchi, Francesca
Abstract : Corrosion of embedded reinforcement is the main cause of deterioration of existing reinforced concrete infrastructure. Corrosion can significantly affect the seismic response and failure mode of reinforced concrete elements, causing premature concrete crushing, size reduction of reinforcement, degradation of mechanical properties of steel and concrete, and degradation and breaking of stirrups. The latter effects trigger inelastic buckling of the longitudinal reinforcement. In this paper, a non-linear finite-element approach, based on multi-layer shell elements and a crack model, is presented. The fixed crack model was developed at the University of Parma (Italy) and is implemented as a subroutine in standard finite-element software. The model incorporates cyclic constitutive laws for steel able to account for buckling of longitudinal rebars and the effects of corrosion. The effectiveness of the proposed model is validated through comparison with experimental data available in the literature. Finally, the capability of the proposed shell modelling to implicitly consider axial force, shear force and bending moment interaction is discussed and comparisons with analytical model and non-linear finite-element analysis results are provided.